BRCA mutations in a cohort of Iraqi patients presenting to a tertiary referral center - Chantal Farra; Christelle Dagher; Lama Hamadeh; Nagi El Saghir; Deborah Mukherji (BMC, 2019)
Abstract Background Unique pathogenic mutations in BRCA1 and 2 genes have been reported in different populations of patients originating from the Middle East region. Limited data are available for the Iraqi population. For many reasons a large number of Iraqi patients present to Lebanon for medical care. This is the first report of BRCA full gene sequencing conducted in a cohort of high-risk patients originating from Iraq. Methods This is a retrospective review of Iraqi patients diagnosed with breast or ovarian cancer referred for BRCA mutation testing at the American University of Beirut from January 2012 to October 2018. Results Of the 42 Iraqi women who underwent genetic testing at our institution, 3 BRCA pathogenic variants were found. Two mutations in BRCA1 c.224_227delAAAG and c.5431C > T and one mutation in BRCA2 c.5576_5579delTTAA were identified. Three other patients had sequence changes considered as variants of undetermined significance. Conclusion In this cohort of high-risk patients, one out of the three pathogenic BRCA variants detected has not previously been reported in the Middle Eastern population. Further studies are required to delineate the spectrum of BRCA mutations in the Iraqi population.